2005
DOI: 10.1123/jpah.2.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Pedometer-Determined Physical Activity Levels of Youth

Abstract: Background:The purpose of this study was to describe the pedometer-determined physical activity levels of American youth.Methods:A secondary analysis of six existing data sets including 1839 (1046 females, 793 males; ages 6 to 18) school-aged, predominantly white subjects from the southwest US. Grade clusters for elementary (grades 1 to 3), upper elementary (grades 4 to 6), middle school (grades 7 to 9), and high school (grades 10 to 12) were created for statistical analysis.Results:Males in grades 1 to 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 22 publications
6
46
1
4
Order By: Relevance
“…In our study, females took approximately 5000 fewer daily steps than males, and older children were less active than younger children; the latter difference has also been observed in healthy children (22). In another finding similar to observations in healthy children, we noted that children and youths with college-educated mothers were more physically active than those with less educated mothers, and children with higher BMI were less active than those with lower BMI.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our study, females took approximately 5000 fewer daily steps than males, and older children were less active than younger children; the latter difference has also been observed in healthy children (22). In another finding similar to observations in healthy children, we noted that children and youths with college-educated mothers were more physically active than those with less educated mothers, and children with higher BMI were less active than those with lower BMI.…”
Section: Discussionsupporting
confidence: 75%
“…In the general population, physical activity has been associated with lower prevalence and incidence of cardiovascular risk factors, such as hypertension, type 2 diabetes, obesity, and hyperlipidemia, and lower levels of physical (22). Dashed lines depict recommended target levels of daily activity (13).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore common practice to report mean daily step counts for boys and girls separately. Other categorisation variables commonly applied where appropriate include age group or school year/grade and BMI since it has been reported that step counts decline with increasing age 39,46,52,75 and BMI. 50,63 Ethnic differences in step counts have also been reported, 47 therefore where relevant it may also be important to report step count data according to ethnicity.…”
Section: Methods Of Data Treatment Analysis and Reportingmentioning
confidence: 99%
“…A number of researchers have excluded data from a particular day, or all of the data from a participant, if participants have reported removing the pedometer for over an hour. 11,[39][40][41][42][43][44][45][46][47][48][49][50] To enhance comparability between studies it is recommended that future studies apply the same protocol of excluding data from a particular day if participants report removing the pedometer for over one hour on that day.…”
Section: Pedometer Wear Timementioning
confidence: 99%
“…Research has shown that adolescent girls are not as physically active as adolescent boys and children (Le Masurier et al, 2005;Trost, Pate, & Sallis, 2002). However, frequent and repeatedly positive situational experiences (of which skill testing in several sports/activities over the course of a school year or years is part) may exert bottom-up effects and eventually lead to changes in one's lifestyle choices (Deci & Ryan, 1985;Vallerand, 2001).…”
Section: Gender and Skill Testingmentioning
confidence: 99%